2017
DOI: 10.1021/acs.jafc.6b04815
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Stability of Curcumin in Aqueous Solutions and Emulsions: Impact of pH, Temperature, and Molecular Environment

Abstract: The utilization of curcumin as a nutraceutical in food and supplement products is often limited because of its low water solubility, poor chemical stability, and low oral bioavailability. This study examined the impact of pH, storage temperature, and molecular environment on the physical and chemical stability of pure curcumin in aqueous solutions and in oil-in-water emulsions. Unlike naturally occurring curcuminoid mixtures (that contain curcumin, demethoxy-curcumin, and bisdemethoxy-curcumin), pure curcumin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
293
1
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 497 publications
(326 citation statements)
references
References 32 publications
16
293
1
16
Order By: Relevance
“…Therefore, the concentrations of curcumin released from BCC films into the acetate buffer were higher than those in the PBS buffer. Degradation should occur very slowly at pH 1-6, whereas degradation could occur at a significantly higher rate in PBS at pH 7.4 due to the instability of curcumin at this pH [18,39]. This degradation could cause the decrease in the concentration of curcumin in the solution that was seen in the release assay after 10 h. This result demonstrates that BC is a good candidate matrix for the controlled release of curcumin.…”
Section: Release Assaymentioning
confidence: 83%
“…Therefore, the concentrations of curcumin released from BCC films into the acetate buffer were higher than those in the PBS buffer. Degradation should occur very slowly at pH 1-6, whereas degradation could occur at a significantly higher rate in PBS at pH 7.4 due to the instability of curcumin at this pH [18,39]. This degradation could cause the decrease in the concentration of curcumin in the solution that was seen in the release assay after 10 h. This result demonstrates that BC is a good candidate matrix for the controlled release of curcumin.…”
Section: Release Assaymentioning
confidence: 83%
“…Pyrazole curcumin, synthesized by using microwave, was found to be more potent inhibitor of CaMKII than curcumin. Molecular docking revealed that hydroxy, carbonyl and pyrazole ring of curcumin, pyrazole and isoxazole derivatives form hydrogen bonds with the protein residues (Table 14). Thus, acute inhibition of CaMKII may be a potential strategy for providing neuroprotection as shown by two independent groups using the CaMKII inhibitor tat-CN21 peptide.…”
Section: Curcumin Pyrazole and Isoxazole Analogs And Their Other Vamentioning
confidence: 99%
“…As expected for hydrophobic compounds, CUR has poor solubility in water at ambient pressure and temperature conditions, and its log P value is between 2.5 and 3.6 . Furthermore, it is soluble in polar organic solvents, such as DMSO . Other molluscicidals, such as niclosamide, are recommended by the WHO for snail control and are also poorly soluble in water …”
Section: Discussionmentioning
confidence: 95%